Role of turbulence and electric fields in the establishment of improved confinement in tokamak plasmas - Van Oost, G.; Bulanin, V.V.; Donné, A.J.H.; Gusakov, E.Z.; Krämer-Flecken, A.; Krupnik, L.I.; Melnikov, A.; Peleman, P.; Razumova, K.A.; Stöckel, J.; Vershkov, V.; Altukov, A.B.; et al. (Вопросы атомной науки и техники, 2006)
An extensive (INTAS) research programme started in 2002 to investigate the correlations between on the one hand the occurrence of
transport barriers and improved confinement in the medium-size tokamaks TEXTOR and T-10 and on the smaller tokamaks FT-2,
TUMAN-3M and CASTOR, and on the other hand electric fields, modified magnetic shear and electrostatic and magnetic turbulence
using advanced diagnostics with high spatial and temporal resolution and of various active means to externally control plasma transport .
This has been done in a strongly coordinated way and exploiting the complementarity of TEXTOR and T-10 and the backup potential of
the three other tokamaks, which together have all the relevant experimental tools and theoretical expertise.